Quality of Board of Directors and Capital Structure Decisions in Malaysian Companies - Ishak, Zuaini; Abdul Manaf, Nor Aziah; Md Kassim, Aza Azlina (Virtus interpress, 2011)
This study examines the relationship between board structure and board process on capital structure decisions of Malaysian public listed companies. The study combines a survey approach and secondary data from the year 2007 to 2009. Based on a sample of 175 companies, the findings reveal that directors’ risk appetite is positively correlated to company leverage while directors’ tenure has negative relationship with leverage. With regards to board process, four variables are identified to be negatively correlated to capital structure which is boards’ risk oversight, performance of independent directors, CEO’s performance evaluation and accessibility of information.